2004
DOI: 10.1095/biolreprod.103.019448
|View full text |Cite
|
Sign up to set email alerts
|

Expression by Transgenesis of a Constitutively Active Mutant Form of the Prolactin Receptor Induces Premature Abnormal Development of the Mouse Mammary Gland and Lactation Failure1

Abstract: Prolactin (PRL) initiates signal transduction by inducing homodimerization of PRL receptor (PRL-R). We have previously developed a mutant form of the PRL-R in which a part of the extracellular domain is deleted. This receptor constitutively activates protein gene transcription. We examined the oligomerization of the mutant PRL-R using two differently epitope-tagged receptors in a coimmunoprecipitation assay. It was shown that mutant receptor dimers were formed in a ligand-independent manner, which may explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…This phenotype is in good agreement with what was observed in virgin Tg mice expressing PRL or a constitutively active PRLR (Wennbo et al 1997, Gourdou et al 2004. From the first gestational/lactational cycle, which turned on expression of autocrine hPRL, more pronounced morphological abnormalities appeared in young WAP-hPRL animals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This phenotype is in good agreement with what was observed in virgin Tg mice expressing PRL or a constitutively active PRLR (Wennbo et al 1997, Gourdou et al 2004. From the first gestational/lactational cycle, which turned on expression of autocrine hPRL, more pronounced morphological abnormalities appeared in young WAP-hPRL animals.…”
Section: Discussionsupporting
confidence: 90%
“…If one considers the stage of mammary differentiation at which it occurs, however, the occurrence (or not) of adenocarcinoma is probably not so surprising. The Met (Wennbo et al 1997), NRL (Rose-Hellekant et al 2003), and b-lactoglobulin (Gourdou et al 2004) promoters were shown to be constitutively active in these models, therefore, PRLR over-activation involved undifferentiated (virgin) mammary glands. At this stage, cell division appeared to be the major component of the actions induced by PRL excess, and both NRL-PRL and Met-PRL models showed that permanent and long-term (O1 year) Figure 9 hPRL expression in other tissues and non-mammary phenotypes.…”
Section: Discussionmentioning
confidence: 86%
“…Any modification to this endocrine equilibrium may impact lobulo-alveolar formation during pregnancy and subsequent lactation (Sternlicht et al, 2006). A similar abnormal mammary phenotype had previously been reported in transgenic mice over-expressing a constitutively active prolactin (PRL) receptor (Gourdou et al, 2004), suggesting that the alterations observed in the mammary glands of OD rabbits may be related to a modification of the PRL pathway. However, no differences in the localization of the PRL receptor, or in the phosphorylation of Stat5, were observed between the two groups during preliminary immunolocalization and Western blot experiments (data not shown), but we cannot exclude an alteration to either the expression of the prolactin receptor or its signaling pathway in response to acute PRL stimulation in the OD group (Nevalainen et al, 2002).…”
Section: Discussionmentioning
confidence: 56%
“…The cellular effects induced by these artificial variants were very similar to those reported in this study for the natural PrlR I146L mutant. Mammary-specific transgenic mice expressing one of these variants were generated (24). Phenotypes included premature over-development of the gland in virgin and pregnant animals, and, after parturition, impaired terminal differentiation, functional failure, and delayed involution.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypes included premature over-development of the gland in virgin and pregnant animals, and, after parturition, impaired terminal differentiation, functional failure, and delayed involution. Unfortunately, this study failed to reveal whether these morphological anomalies developed into mammary tumors because only young animals were used (24). We recently showed that transgenic mice over-expressing Prl in the differentiating/lactating mammary gland developed various benign lesions from the age of approximately 1 year (25).…”
Section: Discussionmentioning
confidence: 99%